A performance da psicagogia no Fedro de Platão - Patricia Lucchesi Barbosa (2022)
Phaedrus is a performative dialogue that takes place under the aegis of the movement. The drama stages the conduction of the young man's soul through the transposition of the rhetoric of the orator, Lysias, to the rhetoric of the philosopher, Socrates. There are three motive forces that act on the soul – necessity, which corresponds to the animal nature of the soul; logos, properly human nature; and love, an aspect of divinity that contributes to the sprouting of the wings of the soul. Just as there are three parts that make up the pair: the charioteer, whose correspondence is the pilot of the soul; the well-bred horse, which follows the charioteer's command, and the unruly horse, which requires restraint. In order to elucidate how the performance of psychagogy takes place, we chose to analyze the thesis in three acts: the images of the soul, the movements of the soul and, finally, the dialectical conduction. It is a kinetic journey that requires a lot of effort in order to achieve the ordering of the movement in an ascending spiral, similar to the movement of the celestial stars. Following the Delphic recommendation of “knowing yourself” requires knowledge of the human soul and its conformations, as well as its limits. Only in this way can rhetoric be used as an art, for only truth can, in fact, persuade, and philosophy is precisely the discursive art that deals with the true being. Thus, the real aim of the whole dialogue is precisely to persuade the young Phaedrus to choose the philosophical life out of love, as well as to persuade us, the readers of Plato, to choose to accompany him in his method of separating and reuniting, until that by “raising our heads” we may glimpse the plain of truth. The movement of psychagogy is, therefore, threefold, with the life of the gods as a point of view, human experience as a paradigm and empty persuasion as its antithesis.